Full-length transcriptome sequencing analysis and characterization, development and validation of microsatellite markers in Kengyilia melanthera - Xiong, Yanli; Yang, Jian; Xiong, Yi; Zhao, Junming; Liu, Lin; Liu, Wei; Sha, Lina; Zhou, Jiqiong; You, Minghong; Li, Daxu; Lei, Xiong; Bai, Shiqie; et al. (Frontiers in Plant Science, 2022)
As a typical psammophyte of the Triticeae, Kengyilia melanthera possesses high feeding potential and great utilization values in desertification control in the Qinghai-Tibet Plateau. However, few gene function and genetic studies have been performed in K. melanthera. In this study, single-molecule real-time sequencing technology was used to obtain the full-length transcriptome sequence of K. melanthera, following the functional annotation of transcripts and prediction of coding sequences (CDSs), transcription factors (TFs), and long noncoding RNA (lncRNA) sequences. Meanwhile, a total of 42,433 SSR loci were detected, with 5′-UTRs having the most SSR loci and trinucleotide being the most abundant type. In total, 108,399 SSR markers were designed, and 300 SSR markers were randomly selected for diversity verification of K. melanthera. A total of 49 polymorphic SSR markers were used to construct the genetic relationships of 56 K. melanthera accessions, among which 21 SSR markers showed good cross-species transferability among the related species. In conclusion, the full-length transcriptome sequence of the K. melanthera will assist gene prediction and promote molecular biology and genomics research, and the polymorphic SSR markers will promote molecular-assisted breeding and related research of K. melanthera and its relatives.